1982
DOI: 10.1149/1.2123727
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Studies on Electrolysis of AlN Dissolved in Molten Salts

Abstract: An exploratory study concerning the solubility and electrolysis of normalAlN in molten salts has been carried out in view of the development of a new process of electrowinning of aluminum with lower energy consumption than the Hall‐Herault process. Aluminum nitride appears soluble in molten Li3N‐normalLiCl and the existence of solubility is supported by thermal analysis, electrical conductivity, and galvanic cell measurements. Chemical analysis of the melt indicates the possibility of existence of aluminum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In the case of AlN electrolysis, the problem includes finding the appropriate electrolytes that can dissolve the very stable AlN (s) . There was a cursory study (Bonomi et al , 1982) which suggested the use of Li 3 N.3AlN.4LiCl electrolyte to dissolve AlN (s) , but no further results have been forthcoming.…”
Section: Thermodynamic Analyses Of Al Extraction From Intermediate Co...mentioning
confidence: 99%
“…In the case of AlN electrolysis, the problem includes finding the appropriate electrolytes that can dissolve the very stable AlN (s) . There was a cursory study (Bonomi et al , 1982) which suggested the use of Li 3 N.3AlN.4LiCl electrolyte to dissolve AlN (s) , but no further results have been forthcoming.…”
Section: Thermodynamic Analyses Of Al Extraction From Intermediate Co...mentioning
confidence: 99%
“…One of the major challenges is to find the appropriate electrolytes that can dissolve the very stable AlN (s) . Bonomi et al (1982) carried out a limited study on the solubility and the electrolysis of AlN in molten salt (Li 3 N-LiCl) bath at 660-700uC. The current efficiency for this system was 83% with a cathodic current density of y1?5 A cm 2 .…”
Section: Extraction Of Al From Al Nitridementioning
confidence: 99%